Bagaimana rumah makan padang berperan dalam proses negosiasi identitas budaya perantau minangkabau di kota bandung? - Mirna Nur Alia Abdullah; Leo Farid Ruhiana; Mughni Nafia Nadhif (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The tradition of migration is an integral part of Minangkabau culture, shaping their social and cultural identity across various regions, including Bandung. In this context, Padang restaurants function not only as culinary businesses but also as social spaces and cultural symbols that play a significant role in the negotiation of migrant identity. This study aims to analyze how Padang restaurants serve as a medium for maintaining, adapting, and reconstructing Minangkabau cultural identity in a heterogeneous urban environment. This research employs a qualitative approach using observation, in-depth interviews, and documentation with restaurant owners and workers in Bandung. The findings reveal that Padang restaurants act as spaces of cultural representation, means of reproducing traditional values, and arenas for adaptation to local culture. The negotiation of identity occurs through daily practices such as language use, food presentation, and social interaction with customers. Thus, Padang restaurants become dynamic symbols reflecting a flexible and adaptive Minangkabau cultural identity in the face of modernization